ChemInform Abstract: Ring Opening of Cyclic Thioimidates in Reaction with Active Methylene Compounds. Issue 4 (January 2016) - Shvydenko, Kostiantyn; Nazarenko, Kostiantyn; Shvydenko, Tetiana; Vlasenko, Yurii; Tolmachev, Andrei; Kostyuk, Aleksandr
Abstract: In the presence of acetic acid anhydride (III), cyclic thioimidates with five‐membered ring [e.g. (II)] react with compounds containing activated methylene group [e.g. (I)] to give aminopropanes [e.g. (IV)] as the major products.